Dukungan orang tua terhadap pembelajaran dalam jaringan (daring) di sekolah dasar selama masa pandemi coronavirus dissease-2019 - Putra, Rifo Syah; Kurniawan, Sandra Bayu; Rintayati, Peduk (Universitas Sebelas Maret, 2021)
Abstract. This study aims to describe parental support for the implementation of online learning during the Covid-19 pandemic at Karangasem 1 elementary school, Surakarta. This research is a qualitative study using a phenomenological research design. The sampling technique used was purposive sampling technique. Data collection techniques using interviews and observations. The data validity test technique used triangulation of sources. Data analysis is obtained from the results of data collection using interactive analysis which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that parents fully supported online learning, forms of parental support included parental involvement in learning and facilities provided by parents for online learning. Obstacles in the implementation of online learning according to parents include stubborn children, using learning facilities other than for learning, and discipline.